2016
DOI: 10.1097/igc.0000000000000815
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Inoperable Vulvar Cancer

Abstract: Vulvar cancer is a rare disease affecting elderly women that is commonly treated with surgery, radiation, and chemotherapy. When tumors compromise the urethra and the anus, or when it is in the groin lymph nodes, radiotherapy, chemotherapy, or both are necessary after surgery.The treatment of locally advanced vulvar cancer has suffered significant changes though the recent decades. So far, the best sequence of treatment is not known: surgery, chemotherapy, or radiotherapy. The radical surgeries usually need a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Concerning the outcome of treatment, the recurrence rate occurred in 35% of the follow-up patients with the median recurrence rate at one year with the groin nodes being the most frequent recurrence site. This recurrence rate corresponded to the previous reports that were in a range of 12–37%, most of them occurring within two years [ 28 ]. The independent risk factors for local recurrences are a higher age, a multifocal tumor, a depth of invasion more than two mm, lymphovascular space invasion, and the presence of groin node dissection [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“…Concerning the outcome of treatment, the recurrence rate occurred in 35% of the follow-up patients with the median recurrence rate at one year with the groin nodes being the most frequent recurrence site. This recurrence rate corresponded to the previous reports that were in a range of 12–37%, most of them occurring within two years [ 28 ]. The independent risk factors for local recurrences are a higher age, a multifocal tumor, a depth of invasion more than two mm, lymphovascular space invasion, and the presence of groin node dissection [ 29 ].…”
Section: Discussionsupporting
confidence: 91%
“… 35 Although there were no changes in the types of surgical procedures employed during our study period, previous studies have shown changes due to the introduction of less radical surgery. 33 36 37…”
Section: Discussionmentioning
confidence: 99%
“…Management of LAVC remains a debate topic due to the rarity of this neoplasm that develops in elderly women with important comorbidities. Treatment of inoperable vulvar cancer has significantly changed in past decades, 12 but there is no standard therapy. Mahner et al 13 and Reade et al 14 did not show superiority of any systemic treatment (neoadjuvant chemoradiation, NACT, and definitive chemoradiation).…”
Section: Discussionmentioning
confidence: 99%